Kurikulum Merdeka: Solution or causation of students' lack of soft skills? - W. Wahyudin; Kania Lisdiana; Alya Arthamevia Solehuddin; Eptina Fatmawati (Inovasi Kurikulum, 2024)
Kurikulum Merdeka is a curriculum concept that allows teachers and students to choose and develop learning content according to their respective needs and conditions. This study aims to critically analyze the implementation of the Kurikulum Merdeka, with a focus on the impact on students' soft skills development. Unlike previous studies that mainly evaluate academic effectiveness, this research examines how well Kurikulum Merdeka succeeds or fails in fostering essential soft skills among students. The method used is a literature study, which involves an in-depth analysis of various relevant written sources. The results show that Kurikulum Merdeka provides mixed results in developing students' soft skills. Although there is an improvement in students' communication skills, the results are still below the expected target. In addition, students' empathy skills did not improve as expected, highlighting significant challenges in instilling empathy through this curriculum. The main barriers identified include a lack of training and support for teachers, limitations in teaching methods, and a lack of support from the home environment and parental involvement. Several strategies need to be implemented to improve the effectiveness of Kurikulum Merdeka. These strategies include improving teacher training, diversifying teaching methods, and increasing parental involvement in education. AbstrakKurikulum Merdeka adalah konsep kurikulum yang memberikan kebebasan kepada guru dan peserta didik untuk memilih dan mengembangkan konten pembelajaran sesuai dengan kebutuhan dan kondisi masing-masing. Penelitian ini bertujuan untuk menganalisis secara kritis implementasi Kurikulum Merdeka, dengan fokusnya pada dampak terhadap pengembangan softskill peserta didik. Tidak seperti penelitian sebelumnya yang terutama mengevaluasi efektivitas akademik, penelitian ini meneliti seberapa baik Kurikulum Merdeka berhasil atau gagal dalam membina softskill yang penting di kalangan peserta didik. Metode yang digunakan adalah studi literatur, yang melibatkan analisis mendalam dari berbagai sumber tertulis yang relevan. Hasil penelitian menunjukkan bahwa Kurikulum Merdeka memberikan hasil yang beragam dalam mengembangkan softskill peserta didik. Meskipun terdapat peningkatan kemampuan komunikasi peserta didik, hasil yang ada masih di bawah target yang diharapkan. Selain itu, kemampuan empati peserta didik tidak meningkat seperti yang diharapkan, sehingga menyoroti tantangan yang signifikan dalam menanamkan empati melalui kurikulum ini. Hambatan utama yang teridentifikasi termasuk kurangnya pelatihan dan dukungan untuk guru, keterbatasan dalam metode pengajaran, dan kurangnya dukungan dari lingkungan rumah dan keterlibatan orang tua. Untuk meningkatkan efektivitas Kurikulum Merdeka, beberapa strategi perlu diterapkan. Strategi ini meliputi peningkatan pelatihan bagi guru, diversifikasi metode pengajaran, dan peningkatan keterlibatan orang tua dalam proses pendidikan.Kata Kunci: implementasi kurikulum; kurikulum merdeka; softskill peserta didik